4.4 problem 6

Internal problem ID [1691]

Book: Differential equations and their applications, 3rd ed., M. Braun
Section: Section 1.9. Page 66
Problem number: 6.
ODE order: 1.
ODE degree: 1.

CAS Maple gives this as type [[_1st_order, _with_linear_symmetries], [_Abel, `2nd type`, `class A`]]

\[ \boxed {\frac {y^{2}}{2}-2 \,{\mathrm e}^{t} y+\left (-{\mathrm e}^{t}+y\right ) y^{\prime }=0} \]

Solution by Maple

Time used: 0.047 (sec). Leaf size: 39

dsolve(1/2*y(t)^2-2*exp(t)*y(t)+(-exp(t)+y(t))*diff(y(t),t) = 0,y(t), singsol=all)
 

\begin{align*} y \left (t \right ) = \left (1-\sqrt {1+c_{1} {\mathrm e}^{-3 t}}\right ) {\mathrm e}^{t} y \left (t \right ) = \left (1+\sqrt {1+c_{1} {\mathrm e}^{-3 t}}\right ) {\mathrm e}^{t} \end{align*}

Solution by Mathematica

Time used: 1.264 (sec). Leaf size: 70

DSolve[1/2*y[t]^2-2*Exp[t]*y[t]+(-Exp[t]+y[t])*y'[t] == 0,y[t],t,IncludeSingularSolutions -> True]
 

\begin{align*} y(t)\to e^t-\frac {\sqrt {-e^{3 t}-c_1}}{\sqrt {-e^t}} y(t)\to e^t+\frac {\sqrt {-e^{3 t}-c_1}}{\sqrt {-e^t}} \end{align*}